Identifikasi Escherichia coli O157:H7 serta Deteksi Gen Shiga Like Toxin 1 dan 2 Asal Feses Hewan, Daging, dan Feses Manusia - Suardana, I Wayan; Artama, Wayan Tunas; Asmara, Widya; Daryono, Budi Setiadi (Jurnal Veteriner; Vol 11 No 4 (2010), 2016)
Escherichia coli O157:H7 with the ability to produce shiga-like toxin was isolated from beef, cattle,chicken, and human feces. Due to its importance to human health, it is necessary to identify the genesencoding the production of shiga-like toxin, stx1 and stx2 respectively to further understand the pathogenesis.Isolation of E. coli was done on Eosin Methylene Blue Agar (EMBA), followed by identification on SorbitolMacConkey Agar (SMAC), latex agglutination test, and H7 antiserum test, respectivelly. The existence ofgenes stx1 and stx2 in E. coli O157:H7 was confirmed molecularly using PCR method with specific primersLP 30/31 and LP 43/44, Stx2 (F)/Stx2 (R) respectively. Escherichia coli O157:H7 was isolated from 22 outof 344 samples (6,4%). Some isolates showed gene stx1 and stx2 was detected in two isolates as indicatedby a 384 bp band (stx1 gene), 584 bp and 1588 bp bands (stx2 gene) respectivelly. The results indicatedthat local isolates E. coli O157:H7 are potential as a zoonoses agent.
Keywords: Zoonoses, E.coli O157:H7, stx1, stx2